Evaluation of English Online Teaching Resources for College Students Based on Grey Correlation Method - Dan Zhang; Tong Zhao (Tehnički Vjesnik, 2022)
Many problems in the evaluation of traditional college English teaching resources have hindered the progress of college English teaching. Under the background of "Internet+", the continuous innovation of college English teaching mode calls for the innovation and perfection of the college English evaluation system. This paper analyzes the evaluation indicators of college studentsꞌ online teaching resources through the introduction of Grey relational analysis. The correlation between various indicators and the evaluation results of college studentsꞌ online teaching resources can be obtained. Some unimportant evaluation indexes can be removed, which simplifies the evaluation of college studentsꞌ online teaching resources. The structure of the model improves the evaluation efficiency of online teaching resources for college students. Therefore, only by strengthening the software and hardware construction of the online teaching platform, updating the teaching concepts of college English teachers, cultivating learners' awareness of autonomous learning, resources in English teaching extensively consult English linguistics and language teaching experts to integrate online teaching resources.